ANALISIS KEPUASAN KONSUMEN TERHADAP LAYANAN DI BANDARA SOEKARNO-HATTA, SERTA IMPLIKASINYA TERHADAP STRATEGI PEMASARAN CITY CHECK-IN TERMINAL DI JAKARTA - Reni Heviandri; Ujang Sumarwan; Retnaningsih Retnaningsih (School of Business, Bogor Agricultural University (SB-IPB), 2009)
The Purpose of this study are: (1) Market segmentation analysis based on Demographic and Psychographic, (2) Customer satisfaction analysis on services in Soekarno-Hatta Airport, (3) Customer perception analysis on services in CCT, and (4) Recommendation on CCT marketing strategy. The analysis was conducted using Descriptive analysis, Cluster, Cochran, CSI and IPA. Based on Customer Satisfaction Index (CSI) analysis of customer satisfaction in check-in services-which will be used as service indicator in CCT, yields satisfaction index value equal to 79.35% means that consumer has satisfied. Customer perception of product attributes in CCT services are: (1) clean and neat check-in service counter, clean and neat check-in service counter, (2) convenient waiting room, (3) departure/arrival information, (4) neat and attractive staf outlook, (5) strategic location, (6) availability of public facilities (mushola, toilet, etc), (7) convenient access to CCT, (8) ease during check-in, (9) fast and save luggage service, (10) fast services, (12) courtesy, (13) professionalism, and (14) clear and accurate information.